The effects of core trainings on speed and agility skills of soccer players - Afyon, Y. A.; Mulazimoglu, O.; Boyaci, A. (International Journal of Sports Science, 2017)
The aim of this study was to examine the effects of core trainings on speed and agility skills of soccer players. 20 subjects in experimental group (age = 23,17 ± 1,86 years, weight = 72,11 ± 3,75kg, height = 174,7 ± 5,04 cm) and 20 subjects in control group (age = 22,03 ± 0, 50 years, body weight = 73,11 ± 6,12 kg, height = 176,7 ± 7,04 cm), summing up 40 amateur licensed soccer players were voluntarily participated in this study. In the study, the speed skills of subjects and control groups were measured by the 30-meter Sprint Test (30mST) and the agility skills were measured by the Illinois Agility Test (IAL) and the T-Drill Agility Test (TDAT). The soccer players in the control group and experimental groups took the pre-test before trainings and post-tests after trainings as speed and agility tests, twice for 8 weeks. After taking the first plot tests, both groups continued their normal training program for 4 days a week for 8 weeks. The subjects in experimental group also took 30 minutes tertian core training program after warm up exercises on 2 training days of the week and then continued the normal training program with the control group in other training days. The paired sample t test analysis was performed between the pre-test and post-test values obtained from the speed and agility tests of the experimental and control groups, and the results were interpreted at a significance level of 0.05. There was no significant difference between the pre-test values of the speed and agility tests of the experimental and control group (p> 0,05). Although the speed and agility post-test scores of the control group showed an improvement compared to the pre-test scores, no significant difference was found between them (p> 0.05). It was found that there was significant differences between the 30mST pre-test (4,53 ± 0,33 sec) and the post-test values (4.44 ± 0,11 sec) (t=0,102; p=0,044), IAL pre-test (16,34±1,15 sec) and the post-test values (14,89±2,84 sec) (t=0,172; p=0,000), TDAT pre-test (9,51±0,17 sec) and the post-test scores (8,11±1,20 sec) of the experimental group (t=0,136; p=0,000). Previous studies have shown that core training has positive effects on the strength development of athletes. According to the results of this study, core trainings which were applied additionally to soccer trainings can contribute positively to the development of players' speed and agility skills.